Electronic Nicotine Delivery Systems and Serum Folate: A Case Study. (November 2019) - Croff, Julie M; Chiaf, Ashleigh L; Hartwell, Micah L; Crockett, Erica K; Tan, Chibing; Teague, Kent
Introduction: In 2018, the US Surgeon General declared youth electronic nicotine delivery systems (ENDS) use as an epidemic. Combustible cigarettes have been shown to adversely affect folate status; however, no study to date has explored how ENDS impact folate status. Methods: In this case study, a white 18-year-old woman was followed for a 1-month period as part of a larger study. During her participation in the study, a self-report of dietary folate consumption and use of alcohol, tobacco, and other drugs (ATOD) was collected. Each week, dried blood spots were collected to assess red blood cell (RBC) and serum folate. Results: During the first 2 weeks of the study, she used ENDS and her serum folate values were depleted in the ranges of 1.91 to 4.39 µg/L. During the third week, when no ENDS were used, her serum folate value was measured at 29.44 µg/L. When ENDS use resumed during the fourth week, her serum folate value fell to 7.50 µg/L. Conclusions: This relationship suggests the need for additional studies on ENDS use and serum folate status, particularly among adolescent women who already have the lowest folate status nationally.